Toward More Sensitive Mobile Phones - Hinckley, Ken; Horvitz, Eric (UIST '01 Proceedings of the 14th annual ACM symposium on User interface software and technology, 2001)
Although cell phones are extremely useful, they can be annoying and distracting to owners and others nearby. We describe sensing techniques intended to help make mobile phones more polite and less distracting. For example, our phone’s ringing quiets as soon as the user responds to an incoming call, and the ring mutes if the user glances at the caller ID and decides not to answer. We also eliminate the need to press a TALK button to answer an incoming call by recognizing if the user picks up the phone and listens to it.